(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The phenomenon of urbanization is neither new norsurprising. During the ages people have tended to cluster together for theirliving and in due course of time areas in habited by human beings for purposesother than agriculture got designated as urban. Of course, invariably there areother attributes too but these are in the nature of afterthoughts andrefinements, and mainly to distinguish the viable units from the non-viableones and do not deserve to be considered as characteristic of the scene. Onemay, indeed, be tempted to make a broad generalization to help identification;clusters where human beings are found together basically and initially forpurely social reasons maybe termed as non-urban; areas where economic necessitybrings them together are generally urban. That is so far as sociologicalfactors go too. Naturally, with the evolution of human society and complexitiesadded to human activity, even the rural areas have gradually begun to gettransformed into economic entities. Agriculture has already become an industryin many countries and is well on its way to show these characteristics in Indiaas well. A way of life is getting changed to a way of living.